Youthful populations an African case study - Pumpkin TV Ltd. ([S.l] : Pumpkin TV Ltd., 2005)
An examination of issues surrounding a young and growing population, using Gambia as a case study. The role of contraception and family planning is discussed, as well as the pressures on resources and the environment
Title from container
Production team: Katie Frampton, Kate Conway, Grant Davies, Simon Ball ; teacher consultant, Raphael Heath
Middle Secondary - Senior Secondary
DVD Format
Keywords: Birth control -- Gambia -- Case studies; Gambia -- Population -- Case studies; Gambia -- Population policy